2021
DOI: 10.1186/s12889-021-12015-w
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial of an mHealth intervention for increasing access to HIV testing and care among young cisgender men and transgender women: the mLab App study protocol

Abstract: Background The number of youth living with HIV in the United States (US) continues to rise, and racial, ethnic, and sexual minority youth including young men who have sex with men (YMSM) and young transgender women (YTGW) bear a disproportionate burden of the HIV epidemic. Due to social and healthcare system factors, many YMSM and YTGW do not seek HIV testing services and are therefore less likely to be aware that they are infected. Mobile health technology (mHealth) has the ability to increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 36 publications
(44 reference statements)
0
3
0
Order By: Relevance
“…HIVST has been shown to be safe and effective in increasing HIV testing rates without affecting condom use, social protection, or treatment inclusion [ 65 , 66 ]. Home testing provides easy access for high-risk individuals who rarely get tested [ 13 ]. Global studies have also shown that no serious side effects associated with HIVST have been reported [ 41 , 67 , 68 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…HIVST has been shown to be safe and effective in increasing HIV testing rates without affecting condom use, social protection, or treatment inclusion [ 65 , 66 ]. Home testing provides easy access for high-risk individuals who rarely get tested [ 13 ]. Global studies have also shown that no serious side effects associated with HIVST have been reported [ 41 , 67 , 68 ].…”
Section: Resultsmentioning
confidence: 99%
“…One study found that among those who had sought testing in the past, 47% preferred home testing over testing in a clinical setting. Acceptability of home testing was 90% among those who rarely tested, underscoring the importance of home testing, especially in at-risk populations who may not have access to clinic testing for a variety of reasons [ 13 , 70 ]. There is evidence that HIV testing at higher frequency is related to a lower risk of HIV infection and is an effective regimen for reducing HIV infection rates [ 71 , 72 , 73 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Once accessed, users upload their completed OraQuick test, which provides real-time HIV results. [1] Usability was assessed using Post-Study System Usability Questionnaire (PSSUQ) and Health Information Technology Usability Evaluation Scale (Health-ITUES), both using a five-point Likert scale to rate system usefulness, information, and interface quality, with higher scores indicating better satisfaction and perceived usability. To examine the association between usability (PSSUQ and Health-ITUES) and user characteristics (e.g., age, education, health literacy), Pearson correlation was performed.…”
Section: Methodsmentioning
confidence: 99%
“…The novel mLab app combines HIV information with a mobile phone imaging feature for interpreting at-home HIV test results. [1] Despite the proliferation of mHealth in health care, many systems have not been rigorously evaluated. We aimed to evaluate the usability of the mLab app for HIV tests and examine how it relates to users' education levels and health literacy.…”
Section: Introductionmentioning
confidence: 99%